INTEGRASI NILAI NILAI CINTA DALAM KURIKULUM PENDIDIKAN KARAKTER BERBASIS ALAM DI MI MUHAJIRIN PALEMBANG - Indah Siti Nurhalizah Nurhalizah; Ahmad Zainuri; Muslim Gani Yasir (STKIP Subang, 2026)
This study aims to examine the integration of love-based values into a nature-based character education curriculum at MI Muhajirin Palembang. The background of this research is grounded in the importance of strengthening character education that not only focuses on cognitive aspects but also encompasses the affective and spiritual dimensions of students. This study employs a qualitative approach using a library research method, with data collected from various relevant scientific literature published between 2021 and 2026. The data were analyzed using content analysis to identify and interpret key concepts related to love-based values, character education, and nature-based learning.The findings reveal that love-based values such as compassion, empathy, care, and social responsibility can be effectively integrated into the character education curriculum through a nature-based approach. Learning activities that involve direct interaction with the natural environment are proven to enhance the internalization of these values in students’ daily lives. Furthermore, the successful implementation of this integration is strongly influenced by the role of teachers as role models and the presence of a supportive school culture. In conclusion, the integration of love-based values into a nature-based character education curriculum represents a relevant and innovative approach to developing students’ character in a holistic, humanistic, and sustainable manner. This study is expected to contribute to the development of character education curricula in madrasahs.